Enacting maturity during adolescence: Extending theory, developing a measure, and considering implications for problem behaviors. Issue 4 (2nd October 2022) - Hoyt, Lindsay Till; Chaku, Natasha; Barry, Kelly; Anderson, Grace; Ballard, Parissa J.
Abstract: A challenge of early adolescence is the "developmental mismatch" between adolescents' need for autonomy and the lack of opportunities to enact maturity via adult-like roles. We identified ways that young people enact maturity, from a youth perspective via focus groups (N = 41, aged 11–17 years), and used data to develop and test a new measure of enacting maturity (EM) using an online survey (N = 420; aged 11–18 years; 58.6% female; 49.5% White). Exploratory factor analysis suggested four internally consistent factors: Independence, Responsibility, Leadership, and Communication ; confirmatory factor analysis resulted in a 21-item scale with adequate model fit. Independence was associated with more substance use and general risk taking while Responsibility and Communication were associated with less substance use and general risk taking. The EM measure is an important first step to understanding if adolescents have opportunities to enact maturity and how this relates to key developmental outcomes.